ANALISIS PENERAPAN SISTEM ADMINISTRASI DATA DAN PROSEDUR PEMUNGUTAN PBB DALAM PENINGKATAN KUALITAS PELAYANAN PAJAK DI KOTA SERANG - Lestari, Dini Martinda; Pertiwi, Sari Putri; Sulistiowaty, Eka Ratna (Gapenas Publisher, 2024)
The source of state revenue can be from several sources, one of which comes from taxes, taxes are divided into two, namely Central Taxes and Regional Taxes. Regional revenues are usually obtained from taxes, one of the influential revenues is the land and building tax, whose collection rights are handed over directly to the city/regency government. However, in the process of data collection and collection, there are still some errors. This study aims to determine how the application of the data administration system and UN collection procedures in improving the quality of tax servants in Serang City The research method used is qualitative research method. This research was conducted by direct interviews with the agency, then an analysis was carried out on the application of the data administration system and UN collection procedures in improving the quality of tax services in Serang City with several data sources and applicable regulations. The data administration system used by the Serang City government is the SISMIOP application, this system has been implemented or used in the process of UN data collection and mass printing in Serang City since 2013, the UN collection procedure in Serang City applies the collection process to be handed over directly to the head of the village and tax officers in the kelurahan. The conclusion of this study is that the UN data collection system and voting procedures in Serang City are still not optimal because there are still many data errors and lack of coordination in the collection process